PENERAPAN MODEL NUMBERED HEADS TOGETHER (NHT) DENGAN MEDIA HANDOUT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PENGANTAR EKONOMI DAN BISNIS (PENELITIAN TINDAKAN KELAS DI SMK NEGERI 1 KARANGANYAR) - -, Sonny Galih Gumelar -; -, Harini -; -, Aniek Hindrayani - (Jurnal Pendidikan Bisnis dan Ekonomi, 2016)
Tujuan Penelitian ini adalah untuk meningkatkan aktivitas dan hasil belajar pada materi Pengantar Ekonomi dan Bisnis kelas XI Pemasaran 2 SMK Negeri 1 Karanganyar tahun ajaran 2015/2016 melalui penerapan model Numbered Heads Together (NHT) dengan media handout. Jenis penelitian ini adalah Penelitian Tindakan Kelas. Subjek penelitian ini adalah siswa kelas XI Pemasaran 2 SMK Negeri 1 Karanganyar tahun ajaran 2015/2016 yang berjumlah 36 siswa. Prosedur penelitian ini meliputi tahap (a) perencanaan, (b) tindakan, (c) observasi, dan (d) refleksi. Berdasarkan hasil penelitian, proses pembelajaran dengan menggunakan model pembelajaran Numbered Heads Together (NHT) dengan media handout dapat meningkatkan aktivitas dan hasil belajar siswa. Terbukti pada siklus I sampai siklus II aktivitas dan hasil belajar siswa mengalami peningkatan. Aktivitas siswa pra siklus pada aspek mental activities 41,67%, oral activities 45,37%, listening activities 55,56% dan writing activities 83,33%. Siklus I pada aspek mental activities 69,44%, oral activities 75,00%, listening activities 88,89% dan writing activities 77,78%. Siklus II pada aspek aspek mental activities 83,33%, oral activities 82,41%, listening activities 91,67% dan writing activities 80,56%. Hasil belajar siswa juga mengalami peningkatan yaitu rata-rata pra siklus 73,08 (presentase ketuntasan 47,22%), siklus I menjadi 77,31 (presentase ketuntasan 80,56%), dan siklus II menjadi 80,95 (presentase ketuntasan 88,89%).ABSTRACKThe purpose of this research is to improve activities and student learning outcomes of the introduction to business economics at class XI Marketing 2 of Vocational High School 1 Karanganyar in the academic year of 2015/2016 through implementation of Numbered Heads Together (NHT) model with Handout media. The type of this research was classroom action reseach. The subject of this research in student at XI Marketing 2 of Vocational High School 1 Karanganyar in the academic year of 2005/2016 with 36 Student. The procedures of this research are (a) planning, (b) action, (c) observation, and (d) reflection. Based on the research result, the learning process with the implementation of Numbered Heads Together (NHT) with Handout media can increase activities and learning outcomes of the student. It could be seen from the cycles I to II have improvement of student activities and student learning outcomes. Pre student activity cycles on the aspects of mental activities 41,67%, oral activities 45,37%, listening activities 55,56% dan writing activities 83,33%. Cycle I, on aspects of mental activities 69,44%, oral activities 75,00%, listening activities 88,89% and writing activities 77,78%. Cycle II on aspect of mental activities 83,33%, oral activities 82,41%, listening activities 91,67% dan writing activities 80,56%. Student learning outcomes are also increased at pre cycle have average value 73,08 (percentage of completeness 47,22%), cycle I becomes 77,31 (percentage of completeness 80,56%), cycle II becomes 80,95 (percentage of completeness 88,89%).